Wobec ziemi. Pomiędzy alienacją a zakorzenieniem - Modrzyk, Ariel; Krajewski, Marek (Kultura i Społeczeństwo, 2022)
The article concerns that aspect of human existence that is frequently neglected both in everyday reflection and in social and humanistic research; namely, earth (soil). It attempts to make a synthetic reconstruction of the relations binding man with the soil preferred in western culture. Apart from identification of the predominant relations, which can be boiled down to it being treated as inanimate matter that is exploited, other concepts are also presented in which soil is perceived as the fundamental medium in sustaining life, change, and the transformation and reshaping of everything that exists. The article comprises three fragments, focusing on practices in cultivation, burial, and celebratory forms of contact with the soil.